2002
DOI: 10.1002/etc.5620210906
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trace organic contaminants in sediment, pore water, and water samples from Onsan Bay, Korea: Instrumental analysis and in vitro gene expression assay

Abstract: Persistent organic pollutants and alkylphenols (APs) were determined in sediment and water samples from Onsan Bay, Korea, by using instrumental analysis and in vitro gene expression cell bioassay. Polycyclic aromatic hydrocabons (PAHs) were the predominant compounds in sediments with concentrations as great as 573 ng/g dry weight. The PAH concentrations were elevated in sediment from inland rivers that flow through Onsan City (mean: 116 ng/g dry wt) and discharge into Onsan Bay. Concentrations of polychlorinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Some investigators have found that the raw extracts from soil or sediments were highly potent in inducing EROD activity; however, in previous studies mass balance was often not reported, or attempts to attribute the potency to known AhR agonists had usually failed (Kannan et al, 2000;Koh et al, 2002). In the present work, mass balance analysis suggested that the chemical composition identified by chemical analytical methods could adequately account for the magnitude of response observed in the EROD bioassay.…”
Section: Mass Balancementioning
confidence: 59%
“…Some investigators have found that the raw extracts from soil or sediments were highly potent in inducing EROD activity; however, in previous studies mass balance was often not reported, or attempts to attribute the potency to known AhR agonists had usually failed (Kannan et al, 2000;Koh et al, 2002). In the present work, mass balance analysis suggested that the chemical composition identified by chemical analytical methods could adequately account for the magnitude of response observed in the EROD bioassay.…”
Section: Mass Balancementioning
confidence: 59%
“…Furthermore, the plastic-particle waste that is prevalent in the oceans can also directly leach BPA into the environment (Sajiki and Yonekubo, 2003). BPA contamination in sediments is widespread: for example, levels have been reported as 0.05 g/g dry weight in Ulsan Bay, Korea (Khim et al, 2001), in Onsan Bay, Korea; as 0.20 g/g dry weight (Koh et al, 2002); and as 0.19 g/g in Germany (Fromme et al, 2002). The four alkylphenols we have identified in lobsters and marine sediments are used together in antioxidant blend formulations for manufacturing rubber and plastic polymers.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrate the total estrogenic activity of environmental samples, regardless of which compounds are responsible for the activity. The results of these studies indicate that estrogenic activity varies widely among sampling sites (Koh et al 2002).…”
mentioning
confidence: 82%
“…In recent years, estrogenic activity in wastewater (Kçrner et al 2001;Kirk et al 2002), river water (Fenet et al 2003), seawater (Koh et al 2002), and sediment (Kannan et al 2000;Koh et al 2002;Fenet et al 2003) has been analyzed by in vitro bioassays. They demonstrate the total estrogenic activity of environmental samples, regardless of which compounds are responsible for the activity.…”
mentioning
confidence: 99%